2009
DOI: 10.17221/37/2008-pps
|View full text |Cite
|
Sign up to set email alerts
|

The importance of monitoring the Ceutorhynchus pallidactylus female flight activity for the timing of insecticidal treatment

Abstract: (2006, 2007, 2008). It was less important and somewhat less complicated to establish the most suitable time for spraying in the case of the chlorpyrifos + cypermethrin combination in comparison with the pyrethroids applied separately. The effectiveness of the tested insecticides was markedly influenced by the time of spraying. The effects of the pyrethroids applied singly achieved results comparable to those of the chlorpyrifos + cypermethrin combination only at the optimal spraying time. The most suitable ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…So, on the basis of this study it is not possible to confirm the previous results that females of C. pallidactylus enter the winter oilseed rape crops markedly later than males. On the other hand in this study the proportions of females were increasing in YWTs during the period of fly activity of the adults in the crop, in agreement with the findings of Seidenglanz et al (2009) and Johnen et al (2010). Klukowski (2006) also studied changes in within-field spatial distribution patterns of male and female C. pallidactylus in the course of crop colonisation.…”
Section: Discusionsupporting
confidence: 89%
See 2 more Smart Citations
“…So, on the basis of this study it is not possible to confirm the previous results that females of C. pallidactylus enter the winter oilseed rape crops markedly later than males. On the other hand in this study the proportions of females were increasing in YWTs during the period of fly activity of the adults in the crop, in agreement with the findings of Seidenglanz et al (2009) and Johnen et al (2010). Klukowski (2006) also studied changes in within-field spatial distribution patterns of male and female C. pallidactylus in the course of crop colonisation.…”
Section: Discusionsupporting
confidence: 89%
“…He found that the males arrived before the females. This tendency was also documented by Seidenglanz et al (2009). However, in this study the first C. pallidactylus females appeared in the crop (more precisely in YWTs located in crops) at the same time as the males in 2013 and 2014.…”
Section: Discusionsupporting
confidence: 76%
See 1 more Smart Citation
“…In order to evaluate the actual damage caused by larvae, an assessment using a six‐point damage rating scale was performed (Table ). For this purpose we used a modified scale described by Seidenglanz . Plants without damage and no recorded weevils were rated as zero.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose we used a modified scale described by Seidenglanz. 16 Plants without damage and no recorded weevils were rated as zero. Slightly damaged plants with tunnels in stems up to 10% of stem length were rated 1, plants with longer tunnels (11-25% of stem) and with low lodging probability were rated 2.…”
Section: Insect Damage Assessmentsmentioning
confidence: 99%